Carbohydrate patterns in the digestive tract of Sparus aurata L. and Psetta maxima (L.) (Teleostei) parasitized by Enteromyxum leei and E. scophthalmi (Myxozoa) - Redondo, Mª José; Álvarez-Pellitero, Mª del Pilar (Parasitology International, 2010)
33 p., figuras, tablas y bibliografía The influence of Enteromyxum spp. infections on the carbohydrate patterns of the digestive tract of gilthead sea bream (GSB) Sparus aurata L. and turbot (TB) Psetta maxima (L.) has been studied. Histochemical stainings to differentiate the types of mucins and lectin-binding assays to detect terminal carbohydrate residues were applied to histological sections of GSB and TB uninfected or infected by Enteromyxum leei and E. scophthalmi, respectively. The number of intestinal GC decreased in severely infected fish in both parasitoses, though changes in mucin patterns were limited to the decrease in the staining intensity for acidic mucins in infected GSB. The TB stomach and intestine lacked histochemically detectable acidic mucins, or sialic acid detectable by SNA, in contrast with their abundance in GSB. Glucose/mannose, fucose and GlcNAc residues were less abundant in both infected hosts with respect to uninfected fish. In contrast, D-Gal and D-GalNAc moieties (detectable by BSL I) increased in most parts of E. scophthalmi-infected TB while decreasing (oesophagus) or remaining unchanged (intestine) in E. leei-infected GSB. The decreasing in the expression of acidic mucins and of sialic acid detectable by SNA in E. leei-infected GSB is remarkable. Differences in the carbohydrate patterns between both hosts could aid to explain the differences in the severity of both enteromyxoses. In addition, the changes induced by Enteromyxum spp. infections in the digestive tract of GSB and TB suggest a role of terminal carbohydrate residues in the parasite-host interaction. Funding for this work was obtained from the Spanish Ministry of Science and Education through the research project AGL2006-13158-C01. M. J. Redondo is recipient of a CSIC I3P contract funded by the European Social Fund. Peer reviewed